Malnutrition and nutritional screening in patients undergoing surgery in low and middle income countries: A systematic review. Issue 4 (25th October 2022) - Jones, Debra; Knight, Stephen R.; Sremanakova, Jana; Lapitan, Marie Carmela M.; Qureshi, Ahmad U.; Drake, Thomas M.; Tabiri, Stephen; Ghosh, Dhruva; Thomas, Maria; Kingsley, Pamela A.; Sundar, Sudha; Maimbo, Mayaba; et al.
Abstract: Background: There is a high incidence of preoperative undernutrition in hospitalised patients in low and middle‐income countries (LMICs), leading to increased postoperative complications, length of hospital stay and early mortality. Review aims are to establish the prevalence of undernutrition and assess the use of validated nutritional screening tools in surgical patients across LMICs. Methods: Protocol was PRISMA compliant and Prospero registered (CRD42019126765). Twelve international databases were searched from January 1990 to April 2021. Included studies were on nutritional screening in adults (≥16 years) undergoing surgery in LMICs. Two researchers screened studies and assessed quality. Prevalence of undernutrition was presented as a weighted percentage with confidence intervals (CI). Results: Of the 4649 records identified, 16 studies ( n = 4032) were eligible. Subjective global assessment (SGA) or patient generated (PG)‐SGA were the tools used most widely. SGA and PG‐SGA showed a high prevalence of undernutrition overall (0.61, 95% CI 0.50, 0.73), with a proportion identified with moderate undernutrition (0.44, 95% CI 0.31, 0.57) or severe undernutrition (0.32, 95% CI 0.19, 0.45). Conclusions: Data show the prevalence of undernutrition in surgical patients as high as three in five patients within LMICs. Results indicate that the SGA is suitable for assessing this group of patients and that it may be the most appropriate tool to use due to its subjectivity and reliability. PG‐SGA although similar includes more symptom assessment, which is important for nutritionally depleted cancer patients. The limited data on validity and reliability of nutritional screening tools in LMICs indicates further research is required.